A phase 2 randomized, controlled trial of the α7 agonist ABT‐126 in mild‐to‐moderate Alzheimer's dementia. Issue 1 (23rd June 2015) - Gault, Laura M.; Ritchie, Craig W.; Robieson, Weining Z.; Pritchett, Yili; Othman, Ahmed A.; Lenz, Robert A.
Abstract: Introduction: The safety and efficacy of the novel α7 nicotinic acetylcholine receptor agonist ABT‐126 were investigated in subjects with mild‐to‐moderate Alzheimer's dementia (AD). Methods: Subjects not currently receiving acetylcholinesterase inhibitors were randomized to ABT‐126 (5 or 25 mg once daily), donepezil 10 mg once daily, or placebo for 12 weeks. The primary efficacy end point was the change from baseline to final evaluation in the 11‐item Alzheimer's Disease Assessment Scale‐cognitive subscale (ADAS‐Cog) total score. Results: A total of 274 subjects were randomized. Although the study did not meet its primary end point, trends toward improvement were seen with ABT‐126 25 mg (least squares mean [standard error] difference from placebo −1.19 [0.90]; one‐sided P = .095) and donepezil (−1.43 [0.90]; one‐sided P = .057) on the 11‐item ADAS‐Cog total score change from baseline to the final evaluation. ABT‐126 5 mg was numerically similar to placebo. An exposure‐response analysis indicated a statistically significant relationship between ABT‐126 exposure and the change from baseline in ADAS‐Cog, with no evidence of a plateau. No clinically meaningful differences in safety were observed among treatment groups. Discussion: Although the ABT‐126 25 mg dose did not demonstrate statistically significant improvement, results of the exposure‐response analysis suggest that higher doses may produce better efficacy, and the safety profile of ABT‐126 in this study supports additional studies with higher doses in subjects with mild‐to‐moderate AD. Clinical trial register number: NCT00948909 .